A Study of Cognitive Results in Marketing and Finance Students. (October 2020) - Ortiz-Rendón, Paola Andrea; Montoya-Restrepo, Luz Alexandra; Munuera-Alemán, Jose-Luis
Background. It is undeniable that human capital is a highly valued resource in today's increasingly competitive and interconnected world.Management education involving decision-making is a fundamental issue in today's education systems. Particularly, the marketing audit improves the decision-making process based on the assessment of themarketing performance and the analysis of themarket results . Althoughmarketing audits are not widely used among organizations yet, marketing control mechanisms have become more important in organizational performance studies and must be integrated into marketing and finance education programs. Method. This quasi-experimental study followed a pretest/posttest design to measure differences in the scores 281 marketing and finance students in Colombia taking part in a game of marketing audit. Results and conclusion. All students significantly improved their higher grades after taking part in the game. Marketing and finance students also improved their responses. For the students in the final semester and for the male and mixed groups, there is insufficient evidence to suggest that the game can improve their cognitive results. Decisions between marketing and finance professionals must be reinforced, to allow academic organizations involved in developing markets and characterized by low levels of competitiveness improve their education levels.